دلالة المعمولات في القرآن الكريم من سورة المائدة إلى سورة الأنعام : دراسة وصفية تحليلية - آدم باوى، رئيسة حسمة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research aims to examine the grammatical conventions in the Holy Quran from chapter ma'idah to Al-An'am. It is a Quranic linguistic issue since each of the grammatical convention has a significant effect towards understanding Holy Quran. It also has lexical and contextual parameters that appear in the structure. The researcher applied analytical descriptive method and followed the theoretical information about the grammatical conventions and its objectives. The Researcher analysed the grammatical conventions found in Surah Al-Ma'ida to Surah Al-An'am to scrutinize their distinctions from each other in terms of meanings or messages. The research found that the declension (Al-ira'b) is one of the main tools of commentators and it is reliable and indispensable which explains the commentary. The views of the classical and modern grammarians on the grammatical conventions are varied. The semantics of the grammatical conventions have a great role in understanding the meanings of the Quran and the Quranic systems and its miraculous understanding of the Qur'anic verses as mentioned in Surah Al-Ma'ida and Surah Al-An'am. There is also a close relationship between the context of the Maqam and the context of the Makaal as mentioned in the Qur'anic verses. Surat Al-Ma'ida and Sura Al-An'am consist of semantics of the grammatical conventions and they have certain connotations.